A survey on the visual perception of humanoid robot - Teng Bin; Hanming Yan; Ning Wang; Milutin N. Nikolić; Jianming Yao; Tianwei Zhang (Biomimetic Intelligence and Robotics)
In recent years, humanoid robots have gained significant attention due to their potential to revolutionize various industries, from healthcare to manufacturing. A key factor driving this transformation is the advancement of visual perception systems, which are crucial for making humanoid robots more intelligent and autonomous. Despite the progress, the full potential of vision-based technologies in humanoid robots has yet to be fully realized. This review aims to provide a comprehensive overview of recent advancements in visual perception applied to humanoid robots, specifically focusing on applications in state estimation and environmental interaction. By summarizing key developments and analyzing the challenges and opportunities in these areas, this paper seeks to inspire future research that can unlock new capabilities for humanoid robots, enabling them to better navigate complex environments, perform intricate tasks, and interact seamlessly with humans.